PENGARUH PERSPEKTIF BALANCED SCORECARD TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH PEMERINTAH PROVINSI SULAWESI SEATAN - A Jamaluddin P, A Jamaluddin P (Perpustakaan dan Penerbitan Unismuh Makassar, 2013)
Researsch aims analyze the effect of Balanced Scorecard perspectives include organizational internal process perspective, financial perspective, public perspective, and personal perspective to transparency, organizational excellence, and accountability in financial management. Collecting data using a questionnaire with a sample study of 250 people working the SKPD in the South Sulawesi provincial government. The analysis tools is the analysis of SEM (Structural Equation Modeling) with the AMOS Ver. 16.0 program. The results showed that the organizational internal process does not significantly affect to transparency, financial perspective significant to transparency, public Perspectives no significant effect on transparency, personal perspective significant to transparency, the organizational internal processes did not significantly influence the organizational excellence, the financial perspective significant to organizational excellence, public Perspectives no significant effect on organizational excellence, personal perspective significant effect on organizational excellence, organizational internal processes significantly influence to accountability, financial perspective no significant effect on accountability, public perspectives no significant effect on accountability, personal perspective no significant effect on accountability, Transparency no significant effect on organizational excellence, transparency significant directly to accountability but becomes insignificant if through organizational excellence and organizational excellence significant effect on accountability.